Energy communities and architectural quality of small historical centres - Antonio Basti; Monica Misceo; Elena Di Giuseppe (Techne)
The text looks at Renewable Energy Communities (RECs) as a tool for implementing strategies that favour local energy transition, with particular focus on inland areas and small historical settlements. These “sensitive” contexts, often situated in landscapes or historical-cultural areas of significant value, require policies to convert to green energy and energy self-sufficiency that evaluate the need for specific actions tied to environmental protection objectives. The study reveals the role RECs can play in urban and landscape regeneration processes in these territories, under the condition that we adopt a holistic and multidisciplinary approach to design, oriented toward reimagining these sites with a view toward relaunching and promoting them.